The Swing-Arm Trellis for Sultana Grapevine Management - Clingeleffer, P.R.; May, P. (South African Journal of Enology and Viticulture, 2017)
The swing-arm trellis, designed to improve mechanical harvesting of Sultana grapevines used for raisin or wine production and to allow partial mechanization of pruning, is described. The trellis consists of seven wires, i.e. a cordon-wire and three wires each Sf>aced evenly in the horizontal and vertical plane and supported by triangular frames attached to the trellis posts. The vines are pruned to cordons that produce shoots that grow upward and attach to the vertical wires. For use as replacement canes, these shoots are placed horizontally by rotation of the frames. The yield of Sultana vines trained in this way was equal to or better than that of control vines trained in the standard manner with canes twisted around a single wire. Over fo'!r seasons, total yield was 1,31 times more for fresh fruit and 1,25 more for sugar. The yield differences occurred mainly in two seasons and were due to the combined effects of more nodes, better bud burst, more fruitful nodes and, consequently, more bunches. The advantages of managing vines trained on the swing-arm trellis are discussed.